The effect of denture cleansers on the color stability, water sorption and water solubility of stained light cured acrylic denture base material (Mustansiria Dental Journal, 2018)
The dirty denture may have undesirable effect on patient's health and ability tosuccessful wear of the denture, if a patient's denture becomes unsanitary, theconsequences may be bad breath, poor esthetic, denture stomatitis and angularcheilitis and the using of the denture cleanser is the solution for this problem but theprolong use of such cleansers may affect the properties of the denture. The aim of thestudy is to observe the effect of denture cleansers on color stability, water sorptionand water solubility of the light cured acrylic resin after their immersion in teasolution.Light curing acrylic resin was prepared and immersed in four types of denturecleansers after there staining with tea then color stability, water sorption and watersolubility of acrylic resin was measured.There were no changes in the stained acrylic properties when the samples wereimmersed in prepared denture cleansers and in the alkaline peroxide cleansercompared to that immersed in the distilled water in respect to color stability, sorptionand solubility of the testing groups.The water sorption, water solubility and color stability of the light cured acrylicresin where immersed in the prepared denture cleanser solutions are in accordancewith the American dental association no.12. The denture cleanser are good andsatisfactory cleanser materials for the acrylic resin denture base and it’s recommendedfor cleansing the prostheses which are cured by light curing method.